2018
DOI: 10.4257/oeco.2018.2201.05
|View full text |Cite
|
Sign up to set email alerts
|

HABITAT CHOICE BEHAVIOR IN Macrobrachium brasiliense (HELLER, 1862) (DECAPODA, PALAEMONIDAE) UNDER LABORATORY CONDITIONS

Abstract: Abstract:The main objective of this study was to analyze the choice behavior of adult individuals of Macrobrachium brasiliense (Decapoda, Palaemonidae) with regard to different substrates and microhabitats in two distinct experiments. The first experiment offered the prawns three samples of substrates with different granulometries: fine sand, coarse sand, and gravel. The second experiment offered three types of microhabitats: aquatic macrophytes, wood fragments, and rocks. In general, the prawns chose the fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This research showed that M. malayanum prefer slightly gravelly sand and gravelly sand substrate types, which is similar to the habitat preference behavior observed for members of Macrobrachium, Litopenaeus, and Crangon genera that prefer fine substrate (Nogueira et al, 2018;Oullette et al, 2003). We presume this substrate preference to be related to their survival in terms of protection and energy minimum required, in other words, M. malayanum are better able to protect itself from potential predators in finer substrate (slightly gravelly sand and gravelly sand) because it is easier to excavate, and requires less energy expenditure (Dall et al, 1990).…”
Section: Discussionsupporting
confidence: 81%
“…This research showed that M. malayanum prefer slightly gravelly sand and gravelly sand substrate types, which is similar to the habitat preference behavior observed for members of Macrobrachium, Litopenaeus, and Crangon genera that prefer fine substrate (Nogueira et al, 2018;Oullette et al, 2003). We presume this substrate preference to be related to their survival in terms of protection and energy minimum required, in other words, M. malayanum are better able to protect itself from potential predators in finer substrate (slightly gravelly sand and gravelly sand) because it is easier to excavate, and requires less energy expenditure (Dall et al, 1990).…”
Section: Discussionsupporting
confidence: 81%
“…Most studies of M. brasiliense addressed its population ecology (García‐Davílla, Alcantara, Vasquez, & Chujandama, ; Mantelatto & Barbosa, ; Oliveira, Sant'anna, & Hattori, ), and there are few published distribution records (García‐Davílla & Magalhães, ; Santos, Castro, & Magalhães, ). Despite the species' wide distribution, there have been few taxonomic reviews (Coelho & Ramos‐Porto, ; Pileggi & Mantelatto, ) and few studies of other aspects of the species' biology such as behavior (Nogueira, Costa, & Almeida, ), feeding behavior (Melo & Nakagaki, ), mass‐length relationships or other measures of physiological condition (Taddei et al, ), reproductive potential (Oliveira, Sant'anna, & Hattori, ), or larval morphology (Pantaleão, Gregatti, Taddei, & Costa, ).…”
Section: Introductionmentioning
confidence: 99%
“…. Despite the species' wide distribution, there have been few taxonomic reviews (Coelho & Ramos-Porto, 1984;Pileggi & Mantelatto, 2012) and few studies of other aspects of the species' biology such as behavior (Nogueira, Costa, & Almeida, 2018), feeding behavior (Melo & Nakagaki, 2013), mass-length relationships or other measures of physiological condition (Taddei et al, 2017), reproductive potential (Oliveira, Sant'anna, & Hattori, 2017), or larval morphology (Pantaleão, Gregatti, Taddei, & Costa, 2011).…”
mentioning
confidence: 99%